Acting Styles of the British New Wave - ŚLIWIŃSKA, ANNA (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2016)
Acting Styles of the British New Wave British New Wave cinema is typically associated with two groups of actors. One includes those with an established position (such as Peter Finch, Laurence Olivier or Dirk Bogarde), and the other those at the beginning of their film career. The latter group seems to be much more interesting in terms of their lives, background and their methods of work. Most of them come from a working-class, non-artistic background (from which the directors of New Wave films asked them to draw inspiration). However, all of them received a solid theatrical education. In this way, a unique collage of skills and experience was created, the elements of which produced a very interesting artistic result. This sheds new light on the phenomenon of the British New Wave: actors, graduates of renowned schools, known from the most famous theatres and troupes (such as the Royal Court Theatre, the Royal Shakespeare Company or the Old Vic) end up in films where they are supposed to play characters from the lower social classes, speak their language and make reference to their own memories and background.